Cardiology: From anatomical and physiological discoveries to the beginnings of the medical specialty in the interior of Rio Grande do Sul - Rigo , Naiane Ronsoni; Kielek , Natalia Demarco; Malacarne , Bruna; Lena , Maísa Diane Turra; Zanin, Elisabete Maria; Wisniewski, Miriam Salete Wilk (Seven Editora, 2024)
In the early days of humanity, the heart was considered the central point of life, both organic and spiritual. Several peoples dedicated themselves to understanding cardiovascular anatomy and physiology, proposing theories that explained the functioning of such a complex system. In Brazil, medical researchers, including Carlos Chagas, suggested considerable advances in scientific research, such as the discovery of the pathophysiology and cardiac manifestations of Chagas Disease, in 1909. In 1943, the Brazilian Society of Cardiology was founded and in 1948 the Society of Cardiology of Rio Grande do Sul, boosting the recognition of the specialty in the country. In this context, this article intends to compose a timeline on cardiology, highlighting aspects of its regional inclusion in a municipality in the north of Rio Grande do Sul. The methodology is based on bibliographic and documentary research on the history of cardiology, taking into account global aspects of the specialty, in addition to deepening its insertion in Erechim-RS, through reports of three cardiologists, considered part of the pioneer group in care in the locality. The report was obtained through a conversation circle open to the community on November 22, 2023, called "History of Cardiology in Erechim" and which marked the 50th anniversary of the specialty in the locality. DOI:https://doi.org/10.56238/sevened2024.016-026